What Predicts a Successful Life? A Life‐course Model of Well‐being. (November 2014) - Layard, Richard; Clark, Andrew E.; Cornaglia, Francesca; Powdthavee, Nattavudh; Vernoit, James
<x xml:space="preserve">Abstract</x> Policy makers who care about well‐being need a recursive model of how adult life‐satisfaction is predicted by childhood influences, acting both directly and (indirectly) through adult circumstances. We estimate such a model using the British Cohort Study (1970). We show that the most powerful childhood predictor of adult life‐satisfaction is the child's emotional health, followed by the child's conduct. The least powerful predictor is the child's intellectual development. This may have implications for educational policy. Among adult circumstances, family income accounts for only 0.5% of the variance of life‐satisfaction. Mental and physical health are much more important.